Peran Media Sosial dalam Memicu Perceraian di Kabupaten Cianjur - Amani Sabila; Alif Firmansyah; Delis Nia nadiyana; Eva Aulia Budiman; Mugianing Putri; Nadiyah Salma Wirahma; Dedi Mulyadi (Journal of Law Perspectives Review, 2025)
This study aims to reveal the role of social media in triggering divorce in Cianjur Regency. The first objective was to identify the impact of social media on divorce, particularly in the context of changes in communication patterns and behavior of married couples. The second objective was to analyze the main factors of social media use that influence divorce decisions, such as infidelity or jealousy triggered by online interactions. The method used was a qualitative approach with survey techniques and data analysis from the Cianjur Religious Court. The results showed that social media contributed to the increasing divorce rate through several factors, with economic factors as the main cause. Consumptive lifestyles displayed on social media often lead to unrealistic expectations and financial pressure in the household. In addition, social media also leads to disrupted communication, jealousy, and online infidelity. The research also found that digital footprints from social media are often used as strong evidence in divorce proceedings, such as screenshots of conversations or posts that show a breach of marital commitment. These findings underscore the importance of digital literacy, emotional management and healthy communication in the household to prevent the negative impact of social media on family harmony.